1994
DOI: 10.1007/bf00297198
|View full text |Cite
|
Sign up to set email alerts
|

Nitinol urethral stents: long-term results in dogs

Abstract: No information has been available to date on the long-term behavior of nitinol (nickel-titanium alloy) urethral stents. In the present study, prostheses of this type were implanted in 18 German shepherd dogs in order to evaluate the reaction of the mucosa, muscles and periurethral tissue. Follow-up examinations performed after 1 week, and 1, 3, 6, 12 and 18 months included urine, macroscopic, radiologic, histologic and scanning electron microscopic analyses. Despite the excellent biocompatibility of the materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
0
25
0
5
Order By: Relevance
“…Both balloon-expandable (BEMSs) and self-expanding metallic stents (SEMSs) are generally used for relieving urinary obstruction in dogs [2,3,7,10,11,18,19]. The major advantage of BEMSs is lack of the foreshortening that occurs with some types of SEMSs, although BEMSs relatively lack flexibility and elasticity.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Both balloon-expandable (BEMSs) and self-expanding metallic stents (SEMSs) are generally used for relieving urinary obstruction in dogs [2,3,7,10,11,18,19]. The major advantage of BEMSs is lack of the foreshortening that occurs with some types of SEMSs, although BEMSs relatively lack flexibility and elasticity.…”
mentioning
confidence: 99%
“…In this study we used the SEMS type with balloon expansion to overcome the limitation of BEMS. One recent study found that SEMSs placed in the urethra of 18 healthy German Shepherds caused no superficial corrosion, infections, dislocations, encrustations, stone formations, or foreign body reactions for 18 months, although progressive pseudopoly- pous mucosal hyperplasia developed over the stent surface in histopathological examinations [11,18]. Another study using polyurethane covered wire stents with paclitaxel-eluting coatings found much favorable clinical outcome in dogs [11,17].…”
mentioning
confidence: 99%
See 3 more Smart Citations